2019
DOI: 10.1017/cjn.2019.167
|View full text |Cite
|
Sign up to set email alerts
|

P.067 Quality of my life: perceptions of boys with Duchenne muscular dystrophy and their parents

Abstract: Background: To attain the most comprehensive view of the quality of life (QoL) of a child with Duchenne Muscular Dystrophy (DMD), the completion of a pediatric QoL measure by the child and his/her parent and the assessment of QoL and health-related quality of life (HRQoL) as separate constructs is crucial. Previous QoL research has not assessed HRQoL as a separate construct. By using the Quality of My Life (QoML) questionnaire, our objective was to describe QoL and HRQoL in boys with DMD based on child-and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The scientific relevance of different contributions demonstrating the impact of NMD on quality of life is undeniable. Chronicity and loss of autonomous functioning due to progressive muscle weakness result in greater dependence on caregivers, which has a negative impact on family functioning; affecting the quality of life of people with NMD at all ages (children, adolescents and adults) and reduces the quality of life of their caregivers (Baiardini et al, 2011;Bendixen et al, 2012;Bhullar et al, 2019;Boyer et al, 2006;Gocheva et al, 2019;Graham et al, 2011;Landfelt et al, 2016;Ortega, 2020;Souares de Moura et al, 2015;Uzark et al, 2012;Zhi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific relevance of different contributions demonstrating the impact of NMD on quality of life is undeniable. Chronicity and loss of autonomous functioning due to progressive muscle weakness result in greater dependence on caregivers, which has a negative impact on family functioning; affecting the quality of life of people with NMD at all ages (children, adolescents and adults) and reduces the quality of life of their caregivers (Baiardini et al, 2011;Bendixen et al, 2012;Bhullar et al, 2019;Boyer et al, 2006;Gocheva et al, 2019;Graham et al, 2011;Landfelt et al, 2016;Ortega, 2020;Souares de Moura et al, 2015;Uzark et al, 2012;Zhi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since many of these conditions are diagnosed in childhood, it is important to study HRQL through lifespan. Previous studies have shown that HRQL is affected on people of all ages with NMD, including children, adolescents, and adults (Baiardini et al, 2011;Bendixen et al, 2012;Bhullar et al, 2019;Gocheva et al, 2019;Graham et al, 2011;Landfeldt et al, 2016;Ortega, 2020;Uzark et al, 2012). In children with NMD, it has been found that HRQL is lower than normative data on a general level and on physical, emotional, social, and school dimensions (Baiardini et al, 2011;Bendixen et al, 2012;Gocheva et al, 2019;Ortega, 2020).…”
mentioning
confidence: 99%
“…Psychosocial aspects of quality of life seem to be the most severely affected in caregivers of children and adults with NMD (Landfeldt et al, 2016;Ortega, 2020;Ortega et al, 2021;Ortiz et al, 2013;Soares de Moura et al, 2015;Zhi et al, 2019). In some cases, parents have even reported even lower levels of QoL than their children (Bhullar et al, 2019). Parents of children with NMD have also reported mental health problems, mainly internalizing problems like anxiety, depression and withdrawn (Ortega et al, 2021).…”
mentioning
confidence: 99%